A Cluster Randomized Controlled Trial to Evaluate HeadCoach: An Online Mental Health Training Program for Workplace Managers. Issue 7 (July 2019) - Gayed, Aimée; Bryan, Bridget T.; LaMontagne, Anthony D.; Milner, Allison; Deady, Mark; Calvo, Rafael A.; Mackinnon, Andrew; Christensen, Helen; Mykletun, Arnstein; Glozier, Nicholas; Harvey, Samuel B.
Abstract : Objective: Mental ill-health is now the leading cause of sickness absence and occupational incapacity in high-income countries. This study evaluated HeadCoach online manager training, designed to improve confidence, and managerial behaviors that create mentally healthy workplaces. Methods: A cluster randomized controlled trial was conducted comparing managers who received HeadCoach ( N = 87) to waitlist control ( N = 123). Managers' confidence and behavior were investigated at baseline, postintervention, and follow-up. Psychological distress of direct reports was evaluated. Results: Confidence significantly increased postintervention only; however, per-protocol analyses indicated a significant improvement for program completers compared with control at both time points. Responsive and preventive behaviors significantly improved. Psychological distress of direct reports remained unchanged. Conclusions: HeadCoach online mental health training is an effective and scalable way to improve managers' confidence and workplace practices around mental health. The impact on direct reports remains unknown.